The Oxford Handbook of Economic and Institutional Transparency 2014
DOI: 10.1093/oxfordhb/9780199917693.013.0003
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy Transparency

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Serious reservations have been raised about their methodology and the interpretation of their results byGeraats (2014).…”
mentioning
confidence: 99%
“…Serious reservations have been raised about their methodology and the interpretation of their results byGeraats (2014).…”
mentioning
confidence: 99%
“…They found that these had policy implications for the better conduct of monetary policy as they fulfilled the rationality properties, including efficiency and unbiasedness. Geraats (2014) drew out the importance of transparent monetary policy in reducing the private sector uncertainty and anchoring their expectations by making it more predictable. The study reviewed the theoretical literature and also studied the conceptual framework for central banks' transparency and empirical evidence of the abovementioned findings.…”
Section: Review Of Literaturementioning
confidence: 99%
“…We refer to this regime as one of "economic transparency" (ET) and in our experiment we will compare welfare under economic transparency with welfare under the pure (no economic transparency) discretionary and commitment regimes. As is well known from Geraats (2002Geraats ( , 2014, a discretionary regime with economic transparency combines a lack of credibility with a lack of flexibility since any policy responses of monetary policy to supply shocks are perfectly foreseen and, therefore cannot affect employment. The inflation bias in the discretionary regime with economic transparency is the same as in the discretionary regime without economic transparency, but the monetary policy response to supply shocks, is larger when there is economic transparency, causing a higher variation of inflation rates without stabilizing employment.…”
Section: +mentioning
confidence: 99%
“…In particular, we explore the role of cheap talk, policy transparency, both cheap talk and policy transparency, and finally economic transparency in overcoming the inflationary bias under discretionary policy. Many of these mechanisms have been studied in the context of Barro-Gordon type monetary policy game set-ups (see, Geraats (2002Geraats ( , 2014 for surveys) and thus the environment we study is appropriate for an analysis of the effectiveness of such mechanisms. We find that of the various mechanisms we study, cheap talk alone results in some welfare improvement relative to the baseline discretionary environment, but the benefits of such a mechanism appear to decline with experience.…”
Section: Introductionmentioning
confidence: 99%